Kurt Grelling - Peckhaus, Volker (Modern Logic Calendar 1995)

Density-functional theory and the v-representability problem for model strongly correlated electron systems - Schindlmayr, Arno; Godby, Rex William (Physical Review B)
Inspired by earlier work on the band-gap problem in insulators, we reexamine the treatment of strongly correlated Hubbard-type models within density-functional theory. In contrast to previous studies, the density is fully parametrized by occupation numbers and overlap of orbitals centered at neighboring atomic sites, as is the local potential by the hopping matrix. This corresponds to a good formal agreement between density-functional theory in real space and second quantization. It is shown that density-functional theory is formally applicable to such systems and the theoretical framework is provided. The question of noninteracting v representability is studied numerically for finite one-dimnsional clusters, for which exact results are available, and qualitatively for infinite systems. This leads to the conclusion that the electron density corresponding to interacting systems of the type studied here is in fact not noninteracting v representable because the Kohn-Sham electrons are unable to reproduce the correlation-induced localization correctly.

A Formal Definition of an Abstract VHDL'93 Simulator by EA-Machines - Börger, Egon; Glässer, Uwe; Müller, Wolfgang (Semantics of VHDL)
We present a rigorous but transparent semantic definition for VHDL corresponding to the IEEE VHDL’ 93 standard [68, 9, 84]. Our definition covers the full behavior of signal and variable assignments as well as the behavior of the various wait statements including delta, time, and postponed cycles. We consider explicitly declared signals, ports, local variables, and shared variables. Our specification defines an abstract VHDL ’ 93 interpreter in the form of transition rules for an evolving algebra machine (EA-Machine) [60]. It faithfully reflects and supports the view of simulation given in the IEEE VHDL ’ 93 standard language reference manual. The definition can be understood without any prior formal training. We illustrate our definition by running the example VHDL program set out in the Introduction to this volume.
Keywords: Transition Rule Formal Verification Variable Assignment Kernel Process Simulation Cycle

[Rez. v.] Friedrich Jaeger: Bürgerliche Modernisierungskrise und historische Sinnbildung. Kulturgeschichte bei Droysen, Burckhardt und Max Weber. Göttingen. Vandenhoeck & Ruprecht 1994 - Süßmann, Johannes (Archiv für Sozialgeschichte)

Built-In Test for Circuits with Scan Based on Reseeding of Multiple-Polynomial Linear Feedback Shift Registers - Hellebrand, Sybille; Rajski, Janusz; Tarnick, Steffen; Venkataraman, Srikanth; Courtois, B. (IEEE Transactions on Computers)

Pattern Generation for a Deterministic BIST Scheme - Hellebrand, Sybille; Reeb, Birgit; Tarnick, Steffen; Wunderlich, Hans-Joachim (ACM/IEEE International Conference on Computer Aided Design (ICCAD'95))

́Ich wäre gerne ein Engel ́. Zu Peter Roos' Demaskerade seines als Kunstwerk verkleideten Geschlechtskörpers - Öhlschläger, Claudia; Bettinger, Elfi (Maskeraden. Geschlechterdifferenz in der literarischen Inszenierung)

Zur Blickpunktbezogenheit sprachlicher Lokalisationen: Der Genese-Effekt - Buhl, Heike M.

Zur blickpunktbezogenen Wissensrepräsentation: Der Richtungseffekt - Herrmann, Theo; Buhl, Heike M.; Schweizer, Karin (Zeitschrift für Psychologie)

Rezension zu Susanne Lummerding: "Weibliche" Ästhetik? Möglichkeiten und Grenzen einer Subversion von Codes. Wien: Passagen 1994 - Öhlschläger, Claudia (Rundbrief Frauen in der Literaturwissenschaft 44: Zensur. Mai 1995)

Orientation and Motion of Tetrahydrofuran in Graphite Intercalation Compounds: Proton NMR Studies of Cs(THF)1.3C24 and K(THF)2.5C24 - Schmidt, Claudia; Rosen, M. E.; Caplan, D. F.; Pines, A.; Quinton, M. F. (The Journal of Physical Chemistry)
Keywords: Physical and Theoretical Chemistry; General Engineering

Shear-Induced Alignment of a Hexagonal Lyotropic Liquid Crystal as Studied by Rheo-NMR - Lukaschek, Michail; Grabowski, David A.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Amphiphilic liquid-crystalline networks — phase behavior and alignment by mechanical fields - Fischer, Peter; Schmidt, Claudia; Finkelmann, Heino (Macromolecular Rapid Communications)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Philosophinnen in der Frauenforschung. Ein Plädoyer für Vernunft und Wissenschaft - Hagengruber, Ruth Edith (Wissenschaftliche Weiterbildung für Frauen)

Amortisation und Herrschergedenken im Burgund des 15. Jahrhunderts - Kamp, Hermann (Memoria als Kultur)

Computergestützte Intervention bei Rechtschreibschwäche: Effekte eines kognitions- und lernpsychologisch orientierten Trainingsprogramms auf Morphembasis bei sehr schwachen Sonderschülern. - Walther, J.; Bigga, Regine; Bischof, H. (Sonderpädagogik)

Conformance Tests of Very Large STEP Files - Lehrenfeld, Georg; Müller, Wolfgang; Wiechers, N. (Proceedings of the 4th EXPRESS User's Group)

Pen-based Interfaces for Engineering Environments - Zhao, R.; Kaufmann, H. J.; Kern, T.; Müller, Wolfgang

Transforming SDL Diagrams Into a Complete Visual Representation - Lehrenfeld, Georg; Müller, Wolfgang; Tahedl, C. (Proceedings of Symposium on Visual Languages)
We investigate a translation of SDL diagrams into the complete visual representation of Pictorial Janus (PJ) programs in order to analyze the specification by visual debugging and animation. We additionally introduce timing concepts to PJ (Timed PJ) for a mapping of the SDL timing statements. The concepts transforming SDL interaction and process diagrams into Timed PJ are outlined by an example sketching the transformation of an Ethernet CSMA/CD protocol specification.
Keywords: Animation; Timing; Debugging; Ethernet networks; Multiaccess communication; Protocols; Computer languages; Prototypes; Environmental management; Visualization

Validation of EXPRESS Models - Müller, Wolfgang; Lehrenfeld, Georg; Wiechers, N.

SINGLE-STAGE AND DOUBLE-STAGE ACOUSTOOPTICAL TI-LINBO3 TE-TM CONVERTERS USED IN WAVELENGTH-SELECTIVE POLARIMETER AND POLARIZATION-INDEPENDENT DEPOLARIZER - REHAGE, M; Noé, Reinhold; HARIZI, C; RICKEN, R (FIBER OPTIC NETWORK COMPONENTS)

Weibliche" Ästhetik? Möglichkeiten und Grenzen einer Subversion von Codes - Öhlschläger, Claudia (Rundbrief Frauen in der Literaturwissenschaft)

Guide to EXPRESS-P - Müller, Wolfgang; Felser, W.; Buijs, F. (Proceedings of the 4th EXPRESS User's Group)
Greenville, South Carolina

Complete Visual Specification and Animations of Protocols - Müller, Wolfgang; Lehrenfeld, Georg; Tahedl, C. (Proceedings of ASP-DAC'95/CHDL'95/VLSI'95 with EDA Technofair)
This article discusses the application of Pictorial Janus (PJ) for the rapid development and analysis of protocols by animation and complete visualization. In order to make PJ applicable in the context of hardware description we first extend PJ by timing facilities (Timed PJ) and introduce an approach for integrating VHDL models into this visual framework preserving the simulation semantics of VHDL. We finally give the example of the specification and animation of a non interlocked protocol.
Keywords: Animation; Protocols; Timing; Computer languages; Electronic mail; Context modeling; Visualization; Control systems; Flow graphs; Trademarks

An Editor for the Rapid Prototyping of EXPRESS-G Models - Zhao, R.; Müller, Wolfgang; Kaufmann, H. J.; Kern, Th.; Buijs, F. (Proceedings of the 5th EXPRESS User's Group)

The Process Modeling Language EXPRESS-P - Müller, Wolfgang; Felser, W.; Wiechers, N.

MULTISTAGE SPECTRAL POLARIMETER WITH GREATER-THAN-28DB STOPBAND ATTENUATION - Noé, Reinhold; REHAGE, M; TIAN, F (ELECTRONICS LETTERS)

Azimuthal Anchoring Energy in Photoinduced Anisotropic Films - Vorflusev, Valery P.; Kitzerow, Heinz-Siegfried; Chigrinov, Vladimir G. (Japanese Journal of Applied Physics)
Most electrooptic effects in liquid crystals require a uniform orientation of the director at the glass substrates. A new method to produce suitable alignment layers is based on the creation of anisotropic polymer films by photopolymerization with linearly polarized light. In the present paper we report on measurements of the anchoring strength of these photo-induced anisotropic films. Using a wedge-cell technique, we find an azimuthal anchoring energy of W ϕ ≈2.3·10 -6 J/m 2 .
Keywords: General Physics and Astronomy; General Engineering

Convolution algebras which are not necessarily positivity-preserving - Rösler, Margit (Applications of Hypergroups and Related Measure Algebras)

Trigonometric convolution structures on Z derived from Jacobi polynomials - Rösler, Margit (Journal of Computational and Applied Mathematics)
Keywords: Applied Mathematics; Computational Mathematics

On the dual of a commutative signed hypergroup - Rösler, Margit (Manuscripta Mathematica)
Keywords: General Mathematics

Classiker und Novitäten. Zur Entwicklung des Konzertrepertoires im 19. Jahrhundert - Grotjahn, Rebecca (Zwischen Wissenschaft und Kunst. Festgabe für Richard Jakoby)

Über die Berechnung von Teilkörpern algebraischer Zahlkörper (Diplomarbeit) - Klüners, Jürgen

Conjugated Polymers for CMOS Compatible Applications - Muller, J.; Mankowski, V.; Hilleringmann, Ulrich; Goser, K.; Holmes, A.; Gelsen, O.; Stern, R. (ESSDERC ’95: Proceedings of the 25th European Solid State Device Research Conference)

Vorwort. "Postmodern(e) wahrnehmen" - was soll das? - Schroeter-Wittke, Harald; Beuscher, Bernd; Sistermann, Rolf (Prozesse postmoderner Wahrnehmung. Kunst - Religion - Pädagogik)

Coherent effects induced by static and time-dependent electric fields in semiconductors - Meier, Torsten; von Plessen, G.; Thomas, P.; Koch, S.W. (Physical Review B)
Coherent effects are analyzed that are induced by homogeneous electric fields in photoexcited semiconductors. Extended semiconductor Bloch equations are presented, which include the applied electric field, in addition to the many-body Coulomb contributions in the time-dependent Hartree-Fock approximation. These equations are solved for a one-dimensional tight-binding model of a semiconductor superlattice. Linear and nonlinear optical signals associated with the coherent field-induced effects are calculated. For the case of a static electric field, the influence of the Coulomb interaction, which is treated on the Hartree-Fock level for a contact potential approximation, on the Bloch oscillations, and on their counterpart in the frequency domain, the Wannier-Stark-ladder, is analyzed. For a time-dependent electric field, dynamic localization, i.e., the localization of electrons due to an oscillating electric field, is analyzed. It is predicted that the dynamic localization should be observable in semiconductor superlattices even in the presence of Coulomb interaction.

Polarization selection rules for quantum beating between light-and heavy-hole excitons in GaAs quantum wells - Meier, Torsten; Smith, G.O.; Mayer, E.J.; Heuckeroth, V.; Kuhl, J.; Bott, K.; Schulze, A.; Bennhardt, D.; Koch, S.W.; Thomas, P.; Hey, R.; Ploog, K. (Solid state communications)
We report results on selection rules and polarization conditions for quantum beating between light hole and heavy hole excitons in GaAs quantum wells. The measurements were conducted using time-integrated degenerate-four-wave-mixing in a three-pulse configuration. By choosing particular polarization configurations of the ultrashort optical pulses exciting heavy and light hole excitons simultaneously, degenerate four-wave-mixing signals show either quantum beating or no modulation at all. The experiments are analyzed using a model that takes into account exciton/exciton interaction.

Dynamic Localization in Anisotropic Coulomb Systems: Field induced Crossover of the Exciton Dimension - Meier, Torsten; Rossi, F.; Thomas, P.; Koch, S.W. (Physical review letters)
The effective dimensionality of excitons can be drastically changed by applying an alternating electric field. On the basis of a full three-dimensional description of both coherent and incoherent phenomena in anisotropic structures it is found that appropriate applied oscillating fields change the exciton wave function from anisotropic three dimensional to basically two dimensional. This effective-dimension change is caused by dynamic localization which leads to an increase of the exciton binding energy and of the corresponding oscillator strength.

Theory of quasi-equilibrium nonlinear optical absorption in semiconductor superlattices - Meier, Torsten; Je, K.-C; Rossi, F.; Koch, S.W. (Applied physics letters)
Quasiequilibrium nonlinear optical absorption spectra are computed for semiconductor superlattices. The theory generalizes the semiconductor Bloch equations to describe anisotropic structures. The equation for the interband polarization is solved numerically and the carrier‐density dependent optical nonlinearities are computed. Starting from excitonic absorption, with increasing density exciton saturation and the development of gain is observed. The dependence of the gain spectra on structural parameters of the superlattice is discussed.

Transient degenerate four-wave-mixing on excitons in GaAs quantum wells - Meier, Torsten; Kuhl, J.; Mayer, E.J.; Smith, G.O.; Bott, K.; Schulze, A.; Heuckeroth, V.; Heller, O.; Cundiff, S.T.; Bennhardt, D.; Koch, S.W.; Thomas, P.; et al. (Laser Physics)

Biexciton Contributions to the Excitonic Nonlinearity in GaAs Quantum Wells - Meier, Torsten; Kuhl, J.; Mayer, E.J.; Smith, G.O.; Schulze, A.; Bennhardt, D.; Koch, S.W.; Thomas, P.; Hey, R.; Ploog, K. (Proceedings of the 22nd International Conference on the Physics of Semiconductors ICPS)

Coherent dynamics of exciton wave packets in quantum wells and superlattices - Meier, Torsten; Feldmann, J.; Koch, M.; von Plessen, G.; Stolz, W.; Thomas, P.; Göbel, E.O. (Proceedings of the 22nd International Conference on the Physics of Semiconductors ICPS)

Polarization dependence of beating phenomena at the energetically lowest exciton transition in GaAs quantum wells - Meier, Torsten; Mayer, E.J.; Smith, G.O.; Heuckeroth, V.; Kuhl, J.; Bott, K.; Schulze, A.; Koch, S.W.; Thomas, P.; Hey, R.; Ploog, K. (Physical Review B)
We report time-resolved degenerate four-wave-mixing experiments on a high-quality single GaAs quantum well. The signals for parallel and cross-polarized exciting pulses show pronounced quantum beats with different frequencies corresponding to the heavy/light-hole splitting and the biexciton binding energy, respectively. Comparison of the experimental data with solutions of the optical Bloch equations for a phenomenological model system shows that these features result from strong contributions of the biexcitonic state. The importance of biexcitons to the nonlinear coherent response of the two-dimension exciton is further confirmed by the frequency dependence of the time-integrated four-wave-mixing signal amplitudes measured for the two polarization geometries.

Das geht zu z/weit. Frömmigkeit und Blasphemie als Problem theologischer Ästhetik - Schroeter-Wittke, Harald (Frömmigkeit und Freiheit. Theologische, ethische und seelsorgerliche Anfragen. Hans-Dieter Bastian zum 60. Geburtstag)

Sounds of Silence. Popmusikalische Kontrapunkte zu Elia - Schroeter-Wittke, Harald; Fermor, Gotthard (Was suchst du hier, Elia? Ein hermeneutisches Arbeitsbuch)

Bist du's Elia? Streiflichter zum homiletischen Gebrauch der Elia-texte im 20. Jahrhundert - Schroeter-Wittke, Harald (Was suchst du hier, Elia? Ein hermeneutisches Arbeitsbuch)

Mit Elia Gottesdienst feiern. Anregungen zur liturgischen Gestaltung von Elia-Texten - Schroeter-Wittke, Harald (Was suchst du hier, Elia? Ein hermeneutisches Arbeitsbuch)

Was suchst du hier, Elia? Ein hermeneutisches Arbeitsbuch. Werner H. Schmidt und Horst Seebass zum 60. geburtstag

Animation zum Schlafen. Predigt (Mk 4,26-29) - Schroeter-Wittke, Harald (Zeitschrift für Gottesdienst und Predigt)

Ostern/Osterfest/Osterpredigt II. Osterpredigt - Schroeter-Wittke, Harald (Theologische Realenzyklopädie)

Ultrafast carrier relaxation and vertical-transport phenomena in semiconductor superlattices: A Monte Carlo analysis - Meier, Torsten; Rossi, F.; Thomas, P.; Koch, S.W.; Selbmann, P.E.; Molinari, E. (Physical Review B)
The ultrafast dynamics of photoexcited carriers in semiconductor superlattices is studied theoretically on the basis of a Monte Carlo solution of the coupled Boltzmann transport equations for electrons and holes. The approach allows a kinetic description of the relevant interaction mechanisms such as intra- miniband and interminiband carrier-phonon scattering processes. The energy relaxation of photoexcited carriers, as well as their vertical transport, is investigated in detail. The effects of the multiminiband nature of the superlattice spectrum on the energy relaxation process are discussed with particular emphasis on the presence of Bloch oscillations induced by an external electric field. The analysis is performed for different superlattice structures and excitation conditions. It shows the dominant role of carrier–polar-optical-phonon interaction in determining the nature of the carrier dynamics in the low-density limit. In particular, the miniband width, compared to the phonon energy, turns out to be a relevant quantity in predicting the existence of Bloch oscillations.

Signatures of Fano-resonances in four-wave mixing experiments - Meier, Torsten; Schulze, A.; Thomas, P.; Vaupel, H.; Maschke, K. (Physical Review B)
Optical transitions into discrete levels coupled to an optically active continuum lead to asymmetrical Fano lines in the linear absorption spectra, reflecting interference between the excitation channels. We investigate the corresponding four-wave-mixing spectra for the nonlinear optical response within a model of noninteracting electrons. Our results show that four-wave-mixing experiments provide a useful tool to identify Fano resonances.

Linear and Non-linear Optical Properties of Semiconductor Superlattices: Excitonic and Field-Induced Effects - Meier, Torsten; Rossi, F.; Je, K.-C; Hader, J.; Thomas, P.; Koch, S.W. (Proceedings of IV International Conference on Optics of Excitons in Confined Systems)
The effective dimensionality of excitons can be drastically changed by applying an alternating electric field. On the basis of a full three-dimensional description of both coherent and incoherent phenomena in anisotropic structures it is found that appropriate applied oscillating fields change the exciton wave function from anisotropic three dimensional to basically two dimensional. This effective-dimension change is caused by dynamic localization which leads to an increase of the exciton binding energy and of the corresponding oscillator strength.

Electric-Field-Induced Exciton Ionization in a GaAs/AlGaAs Superlattice - Meier, Torsten; von Plessen, G.; Koch, M.; Feldmann, J.; Koch, S.W.; Thomas, P.; Göbel, E.O.; Goosen, K.W.; Kuo, J.M.; Kopf, R.F. (Proceedings of IV International Conference on Optics of Excitons in Confined Systems)
We study exciton ionization induced by an axial electric field in a strongly coupled GaAs/Al0.3 Ga0.7 As superlattice at low temperatures. The field-induced ionization times of the heavy-hole 1s exciton in the miniband field regime are determined from transient four-wave-mixing experiments and theoretical model calculations. They are found to lie between the field ionization times of excitons in bulk semiconductors, and in strongly confined quantum well systems.

Quantum beats from biexcitons in narrow quantum wells: polarization and density dependence - Meier, Torsten; Albrecht, T.F.; Schulze, A.; Koch, M.; Bott, K.; Feldmann, J.; Stolz, W.; Kuhl, J.; Mayer, E.J.; Koch, S.W.; Göbel, E.O.; Cundiff, S.T. (Quantum Electronics and Laser Science Conference)
Transient four-wave mixing (TFWM) has been extensively used during the last few years to study exciton dynamics in semiconductors and in semiconductor heterostructures. These studies have provided significant insight into exciton dynamics in both ordered and disordered systems. There are, nevertheless, still certain aspects of the excitonic TFWM response that are not completely understood. In particular, a complete understanding of the polarization and intensity dependences of the signai strength, the decay of the time-integrated signal, and the temporal characteristics of the time-resolved signal has proven elusive. Recent theoretical and experimental work has indicated that exciton-exciton interactions are important.1·2 Such interactions include incoherent processes, such as excitation-induced dephasing, and the formation of biexcitons. Additionally, some of the phenomena result from disorder, making them sample dependent.

Polarization dependence of quantum beats between light-hole and heavy-hole excitons in GaAs quantum wells - Meier, Torsten; Kuhl, J.; Mayer, E.J.; Smith, G.O.; Bott, K.; Heuckeroth, V.; Thomas, P.; Koch, M.; Hey, R.; Ploog, K. (Quantum Electronics and Laser Science Conference)
The appearance of quantum beats (QBs) between heavy-hole (hh) and light-hole (lh) excitons in GaAs quantum wells (QWs) has been observed in many degenerate-four- wave-mixing (DFWM) experiments with subpicosecond optical pulses. Although the variation of the beat amplitude and phase with polarization of the incident pulses was recognized early on, a consistent theoretical interpretation of exciton coherence for the case of simultaneous excitation of hh and lh excitons is still missing.

Schule und Bildungshilfe in den Konzeptionen katholischer Missionsgesellschaften - Freitag, Christine

Handlungsorientierte Medienpädagogik in Beispielen. Projekte und Unterrichtseinheiten für Grundschulen und weiterführende Schulen - Tulodziecki, G.; Schlingmann, A.; Mose, K.; Mütze, Ch.; Herzig, Bardo; Hauf-Tulodziecki, A.

Entwurf eines Drehbuchs für eine Hypermedia-Arbeitsumgebung zum sozialen Lernen - Herzig, Bardo; Mütze, Ch.; Greiff, S.

Erfolgscontrolling unter besonderer Berücksichtigung produktionswirtschaftlicher Aspekte - Betz, Stefan

The Halfspace Method for Causal Structures on Homogeneous Manifolds - Hilgert, Joachim (Semigroups in Algebra, Geometry and Analysis)

Woodhouse, N.M.J. Geometric Quantization (Clarendon Press, 1992) - Hilgert, Joachim (JBer. DMV)

Lie Theory and its Applcations in Physics

Symplectic Convexity Theorems, Lie Semigroups, and Unitary Representations - Hilgert, Joachim; Neeb, K.-H. (Semigroups in Algebra, Geometry and Analysis)

Compression Semigroups of Open Orbits on Real Flag Manifolds - Hilgert, Joachim; Neeb, K.-H. (Monatshefte Math.)

Compression Semigroups of Open Orbits in Complex Manifolds - Hilgert, Joachim; Neeb, K.-H. (Arkiv för mat.)

Groupoid C*-Algebras of Order Compactified Symmetric Spaces - Hilgert, Joachim; Neeb, K.-H. (Japan. J. Math.)

Wiener-Hopf Operators on Ordered Homogeneous Spaces - Hilgert, Joachim; Neeb, K.-H. (J. Funct. Anal.)

Streitfragen der Mathematik in Forschung und Lehre - Hilgert, Joachim (mathematica didactica)

Maximality of Compression Semigroups - Hilgert, Joachim; Neeb, K.-H. (Semigroup Forum)

Methode zur Modellierung der Informationsverarbeitung in Industrieunternehmen - Hornbostel, Dirk

Bessel-type signed hypergroups on R - Rösler, Margit (Probability measures on groups and related structures XI (Oberwolfach 1994))